PENGARUH EXPERIENTIAL MARKETING TERHADAP MINAT BELI ULANG PELANGGAN - Ivone Maulidia Cilesti; Ade Titi Nifita (DIGEST MARKETING, 2018)
Research purpose is to determine the effect of Experiential Marketing on repurchase intention. Independent variable consists of Sense, Feel, Think, Act, and Relate and dependent variable (Y) is repurchasing intention. Research used questionnaire as data gathering instruments. Furthermore, quantitative descriptive method, multiple linier regression analysis is used as an analysis tool. The results showed that experiential marketing simultaneously showed significant effect. Furthermore, those independent variables only Feel, Act, and Relate have significant effect. And dominant variables are Feel and Act. Hence, Restaurant Dapur Kito recomend to create a positive Feel and Relate experience for costumer that gives a good reputation.